Defisiensi antibodi primer dan hubungannya dengan kelainan kulit - Magdalena, Maria; Mappiasse, Alwi (Lembaga Penelitian Universitas YARSI, 2011)
Primary antibody deficiency is the most abnormality found in primary immunodeficiency. It is caused by function defect and cell B development which antibody production. it is commonly found on baby and children, except common variable immunodeficiency (CVID) which mostly on adult. Cutaneous manifestaion caused by primary antibody deficiency, not specific, and not as many as other defeciency like cell T deficiency. Cutaneous abnormality caused by bacterial infection is the main problem beside atopy and autoimmune disease. Immunoglobulin replacement therapy has a important role in primer antibody deficiency management.